2014
DOI: 10.1074/mcp.m113.031377
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 7 Plays a Role in Ribosome Biogenesis and Protein Synthesis

Abstract: It has been shown that SIRT7 regulates rDNA transcription and that reduced SIRT7 levels inhibit tumor growth. This anti-tumor effect could be due to reduced Pol I activity and perturbed ribosome biogenesis. In this study, using pulse labeling with RNA and amino acid analogs, we found that SIRT7 knockdown efficiently suppressed both RNA and protein synthesis. Surprisingly, SIRT7 knockdown preferentially inhibited protein synthesis over rDNA transcription, whereas the levels of both were reduced to similar exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 38 publications
(72 reference statements)
5
95
0
2
Order By: Relevance
“…The volcano plot presented in Fig. 1B depicts the different Sirt7 interactors including Sirt1, some of which have been described before (16,20,21). A full list of Sirt7 interacting proteins identified in this screen is included in SI Appendix, Dataset S1.…”
Section: Resultsmentioning
confidence: 99%
“…The volcano plot presented in Fig. 1B depicts the different Sirt7 interactors including Sirt1, some of which have been described before (16,20,21). A full list of Sirt7 interacting proteins identified in this screen is included in SI Appendix, Dataset S1.…”
Section: Resultsmentioning
confidence: 99%
“…Sirt7 is known to inhibit autophagy through its interaction with mammalian target of rapamycin. 24 Therefore, it is reasonable to hypothesize that Sirt7-dependent TβRI regulation is mediated by autophagy. In this regard, we found that Sirt7 mediates some of its effects by interaction with PICK1.…”
Section: Discussionmentioning
confidence: 99%
“…24 Loss of Sirt7 accelerated TβRI breakdown in rat cardiac fibroblasts and mouse dermal fibroblasts after starvation ( Figure 5A and Figure VIIA in the online-only Data Supplement). Accordingly, we investigated in the next series of experiments whether Sirt7 regulates TβRI protein by modulating the autophagy pathway.…”
Section: Sirt7 Maintains Tβri Protein By Interacting With Protein Intmentioning
confidence: 99%
“…Levels of newly synthesized protein were estimated using a nonisotopic labeling method as described previously (19), with a Click-it HPG Alexa Fluor 488 protein synthesis assay kit (Life Technologies). Briefly, primary bone marrow-derived macrophages were grown for 30 min in RPMI 1640 medium without methionine (Life Technologies) and supplemented with 50 M L-homopropargylglycine (HPG).…”
Section: Methodsmentioning
confidence: 99%